Artificial Intelligence in English Language Learning: Insights from University of Vakinankaratra Engineering, ENS Students, and English Teachers in Antananarivo, Madagascar - ANDRIANJARY Myriam; ANDRIANARIMANANA Jean Claude Omer; RANDRIATEFISON Nirilalaina; RATIARIMANANJATOVO Narindra; ROBIJAONA RAHELIVOLOLONIAINA Baholy (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
Artificial Intelligence (AI) has become an integral part of 21st-century life and is playing a crucial role in foreign language learning, especially in improving students' English proficiency. This article highlights AI’s transformative role in delivering personalized learning experiences, intelligent tutoring, gamified environments, language learning applications, and automated assessments. These tools adapt to individual needs, provide instant feedback, engage learners interactively, and enhance language skill evaluations, leading to greater student engagement and autonomous learning. While AI offers many advantages, potential challenges and issues in its implementation must be considered. How can Artificial Intelligence be utilized to transform English language learning/teaching by offering diverse learning opportunities and improving the educational experience for both students and teachers? In Madagascar, the importance of English learning and teaching is increasing as various centers and institutions strive to promote the language. A survey conducted in July 2024 with 50 engineering students from the University of Vakinankaratra and 10 students from the Ecole Normale Supérieure (ENS) in Antananarivo shows high receptiveness to AI in language learning, with 90% of participants demonstrating a strong understanding of its role. Additionally, surveys from 12 English teachers in Antananarivo revealed that 75% of them recognize the benefits of AI for both teaching and learning. These findings underscore AI's expanding role in English education, its positive influence on language acquisition, and its potential for enhancing teaching methods.